CLEMASTINE, THE H1 HISTAMINE RECEPTOR ANTAGONIST, ALTERS THE HUMAN SEX AND THYROID HORMONAL PROFILES - AHMED A ABD-RABOU; Ahmed, Hanaa h; Eskander, Emad f (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objective: Clemastine is widely used as an antihistaminic drug. However, clemastine effectively acts as an antagonist of H1 histamine receptor, it has significant burden adverse effects causing common nervous system, psychiatric, and gastrointestinal ailments, as well as rare cardiac and immune system disorders. The objective of this study is to investigate whether there is a remarkable impact of clemastine administration on the human hormonal pituitary-thyroid-adrenal axis. Methods: To achieve that, hormonal profile was tested in the sera of males and females treated and untreated individuals with clemastine. This is to measure serum estradiol, follicle-stimulating hormone, luteinizing hormone, prolactin, progesterone, dehydroepiandrosterone sulfate, thyroid-stimulating hormone, triiodothyronine, thyroxine, fasting insulin, and cortisol levels. The circulating hormonal levels were measured quantitatively using enzyme-link immunosorbent assay. Results: We resulted that there were significant differences of the human hormonal profile on clemastine treatment. Conclusion: Hormonal profiling showed that there were remarkable signatures could be of great interest to underline some recommendations and guidelines optimizing the clemastine dosage to avoid burdens associated with the administration of this drug as well as maintain the physiological and psychological performances of both sexes exposing to clemastine during the period of allergic treatment.